O conceito de dignidade em Kant - Lima, Ítalo Clay Tavares de (My University, 2016)
This dissertation aims to analyze the concept of dignity to the Kantian outline. This text begins with the piquiana anthropological concern in conceiving man his place in the cosmos. When Giovani Pico della Mirandola states that the dignity of man emanates from the possibility that he wants to be what you want, and therefore is worthy of admiration, it makes clear the importance of freedom and autonomy for man. Be angel or beast is a genuinely human choice. Henceforth, in Kant the search for elements underlying the dignity of the human person, has as starting point the education of reason toward dignity as it is through education that comes to human dignity, as the act of educating implies humanize. Thinking about education in Kant is related to human behavior (individual) and the moral actions together, as the purpose of education is to order the man before the law and the right so that you can observe justice. Freedom, autonomy and the will are attributes of a properly educated man and knowledgeable of their rights. In addition, the dissertation presents some relations with rousseauian thought in referring to the concept of freedom and human nature. For Kant, the goodness or badness are not aspects determined by the nature. Already Rousseau thinks the act of teaching can be found in the primitive state. Such divergences are widely placed, discussed and analyzed. Clarification (Aufklärung), a leading Kantian concepts, is a turning point for the educational aspect of man as it is in the act to clarify that man happens to make public use of reason. Once cleared, the man begins to exercise his rational nature in order to dignity. There is no doubt that the Kantian thought in general is timeless. Kant became one divider of waters of modernity with an influence on your unquestionable contemporaneity. So what can be concluded on a preliminary basis is the power that education plays in the intellectual and physical training in man. The awareness of merit refers to the fact of being properly educated.
O conceito de dignidade será analisado no presente trabalho sob a luz do pensamento kantiano e, com a preocupação antropológica de Giovani Pico della Mirandola, de concedia ao homem o seu devido lugar no cosmos. Segundo ele, a dignidade do homem emana do seu potencial,dele querer ser o que quiser e, por esse motivo, deixava clara a importância da liberdade e da autonomia para o homem. Ser “anjo” ou “besta” seria uma escolha genuinamente humana. Para Kant os elementos que fundamentam a dignidade da pessoa humana, tem como ponto partida, a educação da razão, pois é por ela que o ser humano é “construído”. O pensamento acerca da educação em Kant é correlacionado com a conduta humana individual e com as ações morais em conjunto, uma vez que, a finalidade da educação é conscientizar o homem para o cumprimento das leis e do direito, para que seja possível a justiça. A liberdade, a autonomia e a vontade são atributos de um sujeito devidamente educado e conhecedor dos seus direitos. Este texto apresenta algumas relações com o pensamento de Rousseau no que se refere ao conceito de liberdade e da natureza humana. Para Kant, a bondade ou a maldade não são aspectos determinados pela natureza. Já Rousseau pensava que o ato de educar podia ser encontrado no estado de natureza. Tais divergências são postas, discutidas e analisadas. O esclarecimento (Aufklärung), um dos principais conceitos kantianos, é um ponto decisivo para entrever o aspecto educativo do homem, pois é no ato de esclarecer que o homem passa a fazer o uso público da razão. Uma vez esclarecido, o homem passa a exercitar a sua natureza racional com vistas à dignidade. Não há dúvidas que o pensamento kantiano de modo geral seja atemporal. Kant se tornou o divisor de águas da modernidade, com uma influência na contemporaneidade inquestionável. Portanto, o que se pode concluir de maneira preliminar é o poder que a educação exerce na formação intelectiva e física do homem. A consciência do ser digno remete ao fato do ser devidamente educado.
Keywords: Kant, Immanuel, 1724-1804; Dignidade; Liberdade; Dignity; Liberty